Filipińskie kino w odcieniach różu - Delimata, Maria (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
This essay discusses two examples of contemporary Filipino cinema – The Blossoming of Maximo Oliveros (Ang Pagdadalaga ni Maximo Oliveros), Auraeus Solito’s directoral debut, and Joel C. Lamangan’s Zsazsa Zaturnnah: Ze Moveeh. More divides than binds these films together, especially in terms of genre. The first is a comedy-drama, the latter – a musical adaptation of a fantasy comic book. What binds them together is the fact that both main characters are bakla – Filipino gays, although the word is very difficult to translate into Polish. It refers both to a “gay“ – a homosexual person who is in a relationship with another homosexual person, as well as a feminized man who performs his own sexuality and identity. Even though it would be very difficult to describe The Blossoming of Maximo Oliveros and Zsazsa Zaturnnah: Ze Moveeh as masterpieces of contemporary cinema, their pertinence should be seen in the courage to speak about the issue of homosexuality in the Philippines and the undeniable uniqueness of showing the social problems of the country in this manner.